2013
DOI: 10.1016/j.jval.2013.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Can the Use of Social Media and Mobile Apps Improve Patient Knowledge of Disease and Health Outcomes? A Systematic Review

Abstract: Intra class correlation coefficients between the countries were high: from 0.89 (England vs. US) through 0.99 (Canada vs. US). ConClusions: This proof of concept study indicates that computer-based choice tasks for the EQ-5D-5L in the general population are feasible and parameter of the choice tasks estimates are generally consistent and logical, and the estimated values are largely consistent between the 4 countries. PP3 Can the Use of soCial Media and Mobile aPPs iMProve Patient Knowledge of disease and heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Interestingly, internet and social media contributed remarkably in the enrichment of participants' information. Actually, a study depending on knowledge of the ophthalmological disorders and other diseases showed that the patients who received social media-based information about their disease had better clinical outcomes if compared to their control peers (Abogunrin & Martin, 2013). Using social networks, such as Facebook and Twitter has the potential to increase the levels of communication among the patients and between patients and healthcare professionals, where feedbacks could be exchanged extensively.…”
Section: Discussion:-mentioning
confidence: 99%
“…Interestingly, internet and social media contributed remarkably in the enrichment of participants' information. Actually, a study depending on knowledge of the ophthalmological disorders and other diseases showed that the patients who received social media-based information about their disease had better clinical outcomes if compared to their control peers (Abogunrin & Martin, 2013). Using social networks, such as Facebook and Twitter has the potential to increase the levels of communication among the patients and between patients and healthcare professionals, where feedbacks could be exchanged extensively.…”
Section: Discussion:-mentioning
confidence: 99%
“…Studies to date are descriptive in nature and do not directly investigate impacts of using social media on communication skills following TBI [81][82][83][84][85][86][87][88][89].It is not known how social media is used by people with TBI or how it might be used in rehabilitation following TBI.…”
Section: Injury (Tbi)mentioning
confidence: 99%
“…The preferred source of information about cross-eye was doctors or healthcare workers for most of the responders. Relatives and friends represented the main source of knowledge about strabismus in some studies [ 14 , 19 ], while in other studies the reported resources were doctors, internet browsers, and social media [ 29 , 30 ]. Unsurprisingly, the internet and social media use to obtain information about strabismus was the least among participants.…”
Section: Discussionmentioning
confidence: 99%